OPTIMALISASI KEBIJAKAN PERLINDUNGAN KONSUMEN DALAM PENGGUNAAN DOMPET VIRTUAL DI ERA DIGITAL - Winda Pebriyanti; Abdul Atsar (Jurnal Hukum dan Bisnis (Selisik), 2021)
The development of the digital era in Indonesia cannot be avoided, this development is alsoinfluenced by world civilization and increasingly advanced ways of thinking. The DigitalAge is a term used in the rise of digital internet networks (particularly computer informationtechnology). The complexity of this online application is easy to access and practical sothat it is very popular with the wider community. Indonesia is experiencing a Digital Agebased on efficiency and internet connectivity). The digital era does not only have greatpotential for the nation's technological advancement, but also changes people's lives. Thisdigital era has a huge impact on human life, this situation itself will be a challenge for thecommunity and also the government regarding the high consumptive power caused by thecurrent digital era. In the current digital era, there are many choices of Virtual Wallets tomake transactions between consumers and sellers, namely payment through non-cashpayments, now it can be a crime if there is no optimization of legal protection policies, oneof which will suffer the most is the community as consumers who use Virtual Wallets inthis digital era. In this research, a question arises: How Consumer Protection LawsOptimize Policies in Using Virtual Wallets in the current Digital Age. Regarding Actnumber 8 of 1999 concerning Consumer Protection and Bank Indonesia Regulations in lineto provide protection for consumer rights. This right is a key to the success of goods / 84services because consumers themselves really prioritize the convenience of using thepayment system, security in the use of the payment system, including safety in using thepayment system